India’s Contribution to Agriculture and Food Sciences through Open Access Literature - G.H., Hemantha Kumar; V., Srinivasa; M., Bhaskara Reddy; B.T., Chandra (DESIDOC Journal of Library & Information Technology, 2011)
The present study attempts to evaluate the initiatives taken by India to make this intellectual output accessible for all by publishing them in open access resources like open access journals and repositories. The results revealed that India is continuously contributing in open access literature as some of the premier institutions, particularly in the agriculture sciences. The position of India in terms of number of journals in the Directory of Open Access Journals (DOAJ) is 5th and in Directory of Open Access Repositories (OpenDOAR) India has 11th place in the world repository. doi: 10.14429/djlit.32.2.1406